The social mission of the Church : orthodox and patristic perspectives - Pătcaș, Sorinel (Array, 2019)
Many theologians and sociologists claim that in order to restore the social and postmodern man’s original image and resemblance to God, turning him into a “complete person,” with spiritual, religious, or cultural needs, a complex theological approach is needed. This approach, known as Social Theology, includes both a social dimension and a theological one in a Chalcedonian unity and morally regulates the relationship between man and society, between Church and modern and postmodern secular society. By means of this term, the Orthodox Church and Theology want to recover the social, just as “secularized culture experiences the recovery of religion, which it has transferred to the private sphere of people’s life;” it summons the social to dialogue, collaboration and mutual responsibility, in order to recover the “contemporary individual.”